Impact of congenital or experimental hypogonadotrophism on the radiation sensitivity of the mouse ovary - Gosden, R.G.; Wade, J.C.; Fraser, H.M.; Sandow, J.; Faddy, M.J. (Human reproduction (Oxford), 1997)
As the numbers of young people making a full recovery from haematological malignancy continue to rise, reproductive science must investigate ways of ameliorating the sterilizing effects of high-dose chemotherapy and total body irradiation. Because there is conflicting evidence as to whether lower serum gonadotrophin concentrations have any protective effect on the gonads, a study was designed to test whether either congenital or experimentally induced hypogonadism reduces the radiosensitivity of the mouse ovary. Test subjects were either homozygous for the hpg locus or animals of normal phenotype treated with a gonadotrophin-releasing hormone antagonist. At 14 days after receiving a single dose of 0.1, 0.2 or 0.3 Gy X-rays or a sham procedure, primordial follicles in the ovaries of the two experimental groups and controls were counted in serial histological sections. The doses at which half of the follicles were lost (LD50) were estimated as 0.11 ± 0.02, 0.19 ± 0.02 and 0.17 ± 0.02 Gy respectively. There was no significant difference between the controls and the antagonist-treated animals, but the congenitally hypogonadal group was unexpectedly more sensitive to radiation. Either way, these results do not support the hypothesis that the ovary is protected from radiation injury by lower gonadotrophin concentrations.